2022
DOI: 10.1136/bmjgh-2022-008862
|View full text |Cite
|
Sign up to set email alerts
|

Self-injected contraceptives: does the investment reflect women’s preferences?

Abstract: Subcutaneous depot medroxyprogesterone acetate (DMPA-SC) is an innovative contraceptive method aimed at meeting women’s unique circumstances and needs, largely due to its ability to be self-injected. Substantial research and advocacy investments have been made to promote roll-out of DMPA-SC across sub-Saharan Africa. To date, research on the demand for DMPA-SC as a self-injectable method has been conducted largely with healthcare providers, via qualitative research, or with highly specific subsamples that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These data show that only up to 17% of current DMPA-SC users across the settings report self-injecting and that among contraceptive nonusers considering use of injectables in the future, less than 12% wished to self-inject. 29 The lack of enthusiasm for self-injection both in the present research as well as the Performance Monitoring and Action survey results could be the result of a number of factors, including lack of awareness due to limited marketing campaigns, insufficient provider training and promotion among health workers, DMPA-SC supply challenges that discourage providers from prescribing and supporting self-injection, among other causes. 29 Fear of self-injection has also been identified as a barrier to self-injection, 30 and this also came up several times in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…These data show that only up to 17% of current DMPA-SC users across the settings report self-injecting and that among contraceptive nonusers considering use of injectables in the future, less than 12% wished to self-inject. 29 The lack of enthusiasm for self-injection both in the present research as well as the Performance Monitoring and Action survey results could be the result of a number of factors, including lack of awareness due to limited marketing campaigns, insufficient provider training and promotion among health workers, DMPA-SC supply challenges that discourage providers from prescribing and supporting self-injection, among other causes. 29 Fear of self-injection has also been identified as a barrier to self-injection, 30 and this also came up several times in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…However, concurrent delivery of the supply-and demand-side intervention components prevents disentanglement of the relative contributions of each. In the context of very low baseline awareness and uptake of a newly introduced method such as DMPA-SC in Nigeria [14], however, such community-based activities are essential for ensuring that service providers receiving didactic instruction also have access to DMPA-SC clients to complete the practical component of the training. It was this combination of instruction with observed practice that was highlighted by many interviewed providers as most valuable for solidifying learnings and con dence to provide SI, and corresponds with best practice in clinical instruction (see, for example, [30]).…”
Section: Discussionmentioning
confidence: 99%
“…Nigeria moved quickly to develop national DMPA-SC guidelines and policies, including a ve-year "roadmap" to scale DMPA-SC nationally [13]. Despite the supportive policy environment, awareness of contraceptive self-injection remains low: While nationally representative information on knowledge, awareness, and practice of contraceptive self-injection are not yet available, the Performance Monitoring for Action (PMA) program estimates that -despite high awareness of injectable contraception -only 21% of women of reproductive age in both Kano and Lagos States had ever heard of contraceptive self-injection as of 2020-2021 [14]. As a result, DMPA-SC comprises just 9.6% and less than 1% of the contraceptive method mix in Kano and Lagos, respectively [15].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the High Impact Practice of engaging men in family planning [ 27 ], we also recommend developing informational materials targeting men and boys to combat negative rumors about DMPA-SC and self-injection and increase male support. Indeed, a recent analysis of population-based data from Burkina Faso, the Democratic Republic of Congo, Kenya and Nigeria found low use of and demand for self-injection; the authors called for more demand generation since they observed that only one country included in the analysis had promotional campaigns about self-injection [ 28 ]. However, before embarking on demand generation campaigns governments need to ensure there is sufficient supply to meet demand.…”
Section: Discussionmentioning
confidence: 99%